Association Analysis of Baking and Milling Quality Traits in an Elite Soft Red Winter Wheat Population. Issue 3 (1st May 2019) - Gaire, Rupesh; Huang, Mao; Sneller, Clay; Griffey, Carl; Brown-Guedira, Gina; Mohammadi, Mohsen
Abstract : Although grain yield is the most important trait for growers, milling and baking industries demand high‐quality and scab‐free grains for various end products. To accelerate breeding of wheat ( Triticum aestivum L.) cultivars with high grain quality, genetic dissection of quality traits is necessary. Genome‐wide association studies (GWAS) were conducted to identify genomic regions responsible for milling and baking quality traits in soft red winter wheat (SRWW). Seven quality traits were evaluated in two locations and 2 yr for 270 elite SRWW lines. These traits include flour yield, softness equivalent, flour protein, and four solvent (lactose, sodium carbonate, sucrose, and water) retention capacity measurements. In this study, 27, 449 single nucleotide polymorphism (SNP) markers were developed by using both genotyping‐by‐sequencing and 90K SNP array technologies. A linear mixed model in GWAS, accounting for population structure and kinship, was fitted to identify 18 [−log( P ) ≥ 4.0] genomic regions on 12 different chromosomes associated with the quality traits. Only one of these associations seems to be a previously identified quantitative trait locus, whereas others are novel associations. The most significant associations for quality traits were identified on chromosomes 1B, 2A, 2B, 4B, 5A, 7A, and 7D. Candidate gene searches, facilitated by the wheat genome assembly, led us to the identification of putative genes related to SRWW quality traits including fasciclin‐like arabinogalactan. The results of this study can be used in developing high‐quality SRWW varieties for the eastern region of the United States.